2004
DOI: 10.3959/1536-1098-60.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Dendroclimatic Analysis of White Spruce at its Southern Limit of Distribution in the Spruce Woods Provincial Park, Manitoba, Canada

Abstract: We examined the radial growth-climate association of a disjunct population of white spruce (Picea glauca (Moench) Voss) at its southern limit of distribution. Forty-four white spruce tree islands were sampled over four mixed-grass prairie preserves in the Spruce Woods Provincial Park located in the forestprairie boundary of southwestern Manitoba. Reduced radial growth occurred during the 1910s, 1930s, early 1960s, and the late 1970s to the early 1980s and corresponded to periods of drought on the Canadian prai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…The weak response to monthly precipitation as well as the lack of correlation with the annualized periods of precipitation suggest that white spruce trees benefited from the moderated microclimate of aspen groves. These results are very much in contrast to white spruce growing in pure tree island stands which had a strong and direct association with precipitation [24]. The reduced effect of drought stress on white spruce supports the stress gradient hypothesis in which facilitative interactions between tree species are expected under harsher environmental conditions [6][7][8][9].…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…The weak response to monthly precipitation as well as the lack of correlation with the annualized periods of precipitation suggest that white spruce trees benefited from the moderated microclimate of aspen groves. These results are very much in contrast to white spruce growing in pure tree island stands which had a strong and direct association with precipitation [24]. The reduced effect of drought stress on white spruce supports the stress gradient hypothesis in which facilitative interactions between tree species are expected under harsher environmental conditions [6][7][8][9].…”
Section: Discussionmentioning
confidence: 42%
“…Therefore, temperature induced drought stress during the summer of the current year can negatively affect growth, and this was also observed in white spruce growing in pure stands [24,39]. It is unclear why growth was negatively correlated with the spring and early growing season months as well as the annualized periods of river discharge.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The prevailing regional climate of the aspen parkland and mixed-grass prairie in southwestern Manitoba is characterized by low precipitation, high summer temperatures, and dry winds, any of which may be limiting factors to plant distribution and growth (Coupland 1950). For instance, previous studies which examined the radial growth-climate association of White Spruce [Picea glauca (Moench) Voss] in the aspen parkland region demonstrated that growth was restricted by moisture deficiency exacerbated by temperature-induced drought stress (Chhin et al 2004).…”
mentioning
confidence: 99%
“…Autoregressive modeling, therefore, makes observations independent to meet the condition of most statistical analyses. Furthermore, autoregressive modeling removes low-frequency variation and enhances the common growth signal, which is usually best correlated with yearly climatic fluctuations (Linderholm et al 2003, Chinn et al 2004). …”
Section: Tree-ring Analysismentioning
confidence: 99%